Performance, persistence and benchmarks of selected South African unit trusts for the period 1998-2002 - G. Oldham; J. A. Kroeger (South African Journal of Business Management, 2005)
Fund managers in the South African unit trust industry have an objective of generating strong alpha returns, meaning average annual returns above the respective benchmark. This paper analyses the performance of twenty South African unit trusts, selected from various sectors over the 1998 – 2002 period. In all cases the benchmark used by the funds is the Johannesburg Stock Exchange All Share Index. The well-known Capital Asset Pricing Model and a three-factor Arbitrage Pricing Theory model are used in the analysis. The result shows that only four funds of the twenty analysed were able to generate a superior performance in one or more years of the five-year period. Individual unit trusts were unable to perform consistently for any length of time. The failure of the funds to meet their objective is further analysed in terms of the appropriateness of the JSE All Share Index as the benchmark. In some cases the index was not an appropriate benchmark to measure persistence in performance and sector indices were preferable. In a cross-sectional portfolio analysis there was evidence of overall persistence in performance but this was of short duration, related more to negative than positive persistence in performance. Overall, the results of the analysis do not produce convincing evidence that unit trust fund managers were able to generate consistent above average returns to their investors. Furthermore, it may be preferable from an investor's viewpoint if fund managers were to target an absolute rather than a relative benchmark.
Keywords: 650